Psychological, cultural, social and health variables affecting the personality of the retired: research in social anthropology - Hteem, Ali H. (Al-Adab Journal, 2022)
The research topic dealt with psychological, cultural, social, health, economic and political variables affecting the status and personality of the retiree. As for the importance of the study, it stems from an important angle, which is the lack of studies on this group in Iraqi society on the one hand, and the study of its conditions on the other hand; As its problems have become a widespread social concern in society, in addition to the psychological, social and cultural risks these retirees pose to the retiree’s personality, his family and his community. As an integrated social unit affected by various variables.